An integrated analysis of the impact of gender diversity on innovation and productivity in manufacturing firms: Prepared for the institutions for development sector - Juan Miguel Gallego; Luis H. Gutiérrez Urdaneta (Inter-American Development Bank (IDB), 2018)
This paper presents evidence of the effects of gender diversity on firm innovation outcomes and their productivity in Colombian manufacturing firms, by extending a CDM model to include women's participation in science, technology and innovation (STI) activities and production processes. The paper makes a methodological contribution by taking into account potential endogeneity issues of women's participation in STI and innovation behavior. An upward bias of the impact of gender diversity on innovation might arise because more dynamic and innovative managers, knowing the value of gender diversity, may also hire more women in STI. The paper addresses the endogeneity concerns with a Tobit specification of the firm's decision to employ women in STI by instrumenting it with the share of total women in the workforce in the industry or the region where the firm is located. The main results indicate that firms with a larger share of women in the knowledge creation and innovation process might increase their innovative behavior. It also presents evidence of a differentiated effect of gender diversity by type of innovation. Women's participation has a larger effect on technological innovation than on organizational innovation. Finally, gender diversity drives firm productivity, even after controlling for the effect of innovation on the production process. These results are important for developing countries where women's participation in STI activities is extremely low. In Colombia, for example, only 6 percent of STI employees are women, a very low figure compared with the 21 percent participation of women in industry and even lower compared with the 52 percent of women in Colombia's total work force. These figures and this paper's results should open up discussion on policies to promote women's participation in the labor force in manufacturing firms, specifically in the knowledge creation processes.
Keywords: J16; J24; J82; O30; O31; 330; CDM; diversity; gender; innovation; women